Study on rock-breaking characteristics of constant section and spherical tooth hob with the aid of slot produced by water jet - Zhang, Xuhui; Long, Kang; Tan, Tao; Li, Sijia; Tan, Lian Lian (Wroclaw University of Technology, 2024)
In order to analyze and compare the rock-breaking characteristics of constant section hob (CS hob) and spherical tooth hob (ST hob) with the aid of slot produced by water jet, a linear cutting models of granite using two types of hobs under the slot conditions were established using the finite element method. The cutting forces, rock-breaking states, and specific energy consumption of hobs were calculated. The research results revealed that during the cutting process, both types of hobs can induce surface and internal tensile cracks in the rock. There exists a critical cutting width for each type of hob, within which the tensile cracks can extend to the slot, promoting rock fragmentation and generating large rock chips. Under the slot conditions, the vertical and rolling forces on ST hob were found to be smaller than those on CS hob. Moreover, the cutting force of the hob can be greatly decreased by using the proper cutting width. When the hob can effectively utilize the slot for breaking rock, their specific energy consumption is significantly lower than it would be without the slot, which greatly improves the effectiveness of cracking rocks. Addi-tionally, it was discovered that the specific energy consumption of the ST hob was lower than the CS hob’s, indicating that with the aid of slot produced by water jet, the rock-breaking efficiency of ST hob is higher than that of CS hob.
Mining Science, Vol. 31, 2024, s. 61-79
Keywords: mining; geology; geo-engineering